Atomic layer deposited α-Ga2O3 solar-blind photodetectors. (6th September 2019) - Moloney, J; Tesh, O; Singh, M; Roberts, J W; Jarman, J C; Lee, L C; Huq, T N; Brister, J; Karboyan, S; Kuball, M; Chalker, P R; Oliver, R A; et al.
Abstract: Low temperature atomic layer deposition was used to deposit α -Ga2 O3 films, which were subsequently annealed at various temperatures and atmospheres. The α -Ga2 O3 phase is stable up to 400 °C, which is also the temperature that yields the most intense and sharpest reflection by x-ray diffraction. Upon annealing at 450 °C and above, the material gradually turns into the more thermodynamically stable ε or β phase. The suitability of the materials for solar-blind photodetector applications has been demonstrated with the best responsivity achieved being 1.2 A W −1 under 240 nm illumination and 10 V bias, for the sample annealed at 400 °C in argon. It is worth noting however that the device performance strongly depends on the annealing conditions, with the device annealed in forming gas behaving poorly. Given that the tested devices have similar microstructure, the discrepancies in device performance are attributed to hydrogen impurities.